2023
DOI: 10.18103/mra.v11i2.3517
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Spirituality as Moderators between Several Concerns and Psychological Distress during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has led to psychological stress caused by several threats such as concerns for health, economic problems, and several others. This study aims at exploring if inner resilience and belief in spiritual support may moderate the relationship between the concerns, on one side, and distress and the attitudes towards anti-COVID-19 vaccines, on the other side. We conducted a study involving 235 participants through an online survey from March to April 2021 in Italy, immediately after the last lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…For example, short term and long-term beneficial effects of spirituality (positive religious coping and perceived spiritual support/PSS) were evident in prospective studies on patients following open-heart surgery [26][27][28]. A new Italian study showed that resilience moderated the link between COVID-19 related concerns and psychological distress during the pandemic, especially among the participants who scored high in PSSS [29]. Religious beliefs are thought to impact psychological, practices are thought to impact biological, and religious community is thought to impact social health of individuals [30].…”
Section: Perceived Spiritual Supportmentioning
confidence: 99%
“…For example, short term and long-term beneficial effects of spirituality (positive religious coping and perceived spiritual support/PSS) were evident in prospective studies on patients following open-heart surgery [26][27][28]. A new Italian study showed that resilience moderated the link between COVID-19 related concerns and psychological distress during the pandemic, especially among the participants who scored high in PSSS [29]. Religious beliefs are thought to impact psychological, practices are thought to impact biological, and religious community is thought to impact social health of individuals [30].…”
Section: Perceived Spiritual Supportmentioning
confidence: 99%
“…Studies conducted in different national and religious contexts have underscored the decisive supportive role played by spirituality in providing responses to the insecurities caused by the contagion during the health emergency. While the pandemic exacerbated states of existential distress (Upenieks 2022) and vaccine skepticism motivated by religious reasons (Zarzeczna et al 2023), spirituality proved useful in counteracting emotions of fear, anxiety, loss of hope (Buchtova et al 2022), depressive symptoms (de Souza et al 2023) and stress (Kosic et al 2023), in grieving the loss of a family member (Biancalani et al 2022) or in fostering individual practices such as praying at home (Apergis et al 2023), with consequences differentiated according to a wide variety of factors such as age (Keisari et al 2022), socioeconomic status (Safdar et al 2023) or health status (Durmuş and Durar 2022). But survivors of such crisis situations and dramatic episodes may activate sensemaking processes that involve a revision of one's value orientation, stimulating innovative spiritual reflection on life and death, the effect of which is a change, even a profound one, in personal priorities and aspirations (Lee et al 2022).…”
Section: Introductionmentioning
confidence: 99%